Bully Victimization Among Children With Attention-Deficit/Hyperactivity Disorder: A Longitudinal Examination of Behavioral Phenotypes. (June 2020) - Winters, Rebecca R.; Blake, Jamilia J.; Chen, Siqi
Children with Attention-Deficit/Hyperactivity Disorder (ADHD) are at a higher risk of experiencing bully victimization compared with peers with and without disabilities. Yet the association between ADHD subtypes and bully victimization is not well understood. The current study examines which set of behaviors related to ADHD subtypes is influential in determining whether students are victimized. Using a latent class growth analysis, students with ADHD in a nationally representative special education sample ( n = 291) were grouped by victimization trajectory. Latent class analysis revealed three victimization profiles. Approximately one third of participants (35%) experienced moderately high victimization decreasing over time. A slightly larger group reported consistently low victimization (39%), and one fourth (25%) reported consistently high victimization. Behaviors representing inattention and hyperactivity/impulsivity were examined as covariates in the model. Hyperactive/impulsive behaviors were predictive of latent class assignment, initial victimization, and the trajectory of victimization. Study limitations are discussed. Recommendations are made to inform the creation of interventions tailored for students who have ADHD.